Groundwater response to tidal fluctuations in a leaky confined coastal aquifer with a finite length. Issue 19 (30th July 2019) - Zhao, Zhixue; Wang, Xiaoguang; Hao, Yonghong; Wang, Tongke; Jardani, Abderrahim; Jourde, Herve; Yeh, Tian‐Chyi Jim; Zhang, Ming
Abstract: The study on the hydraulic properties of coastal aquifers has significant implications both in hydrological sciences and environmental engineering. Although many analytical solutions are available, most of them are based on the same basic assumption that assumes aquifers extend landward semi‐infinitely, which does not necessarily reflect the reality. In this study, the general solutions for a leaky confined coastal aquifer have been developed that consider both finitely landward constant‐head and no‐flow boundaries. The newly developed solutions were then used to examine theoretically the joint effects of leakage and aquifer length on hydraulic head fluctuations within the leaky confined aquifer, and the validity of using the simplified solution, which assumes the aquifer is semi‐infinite. The results illustrated that the use of the simplified solution may cause significant errors, depending on joint effects of leakage and aquifer length. A dimensionless characteristic parameter was then proposed as an index for judging the applicability of the simplified solution. In addition, practical application of the general solution for the constant‐head inland boundary was used to characterize the hydraulic properties of a leaky confined aquifer using the data collected from a field site at the Seine River estuary, France, and the versatility of the general solution was further justified. Abstract : A more general and rigorous solutions for a leaky confined coastal aquifer have been developed considering both finitely landward constant head and no‐flow boundaries, which covered existing models. The solutions illustrated that both the leakage and aquifer length have significant effects on the hydraulic head fluctuations, and the use of the previous simplified solution that assumes the aquifer is semi‐infinite and may cause significant errors. A dimensionless characteristic parameter was proposed as an index for judging the applicability of the simplified solution.